Bài 2:
b) (P): y = ax^2 + bx + c (đk: a # 0)
A(1; 0) ∈ (P) => 0 = a + b + c (1)
B(3; 0) ∈ (P) => 0 = 9a + 3b + c (2)
Ta có: Δ = b^2 - 4ac
Đỉnh I nằm trên đt y = -1 => Đỉnh I có tung độ y = -1
Với y = -1 <=> -Δ/4a = -1
<=> 4ac - b^2 = -4a
<=> 4a(c + 1) = b^2 (3)
Từ (1), (2), (3) ta có hpt: a + b + c = 0 và 9a + 3b + c = 0 và 4a(c + 1) = b^2
<=> c = - a - b và 9a + 3b - a - b = 0 và 4a(c + 1) = b^2
<=> c = -a - b và 8a + 2b = 0 và 4a(c + 1) = b^2
<=> c = -a - b và b = -4a và 4a(c + 1) = b^2
<=> c = - a - 4a và b = -4a và 4a(c + 1) = b^2
<=> c = -5a và b = -4a và 4a(- 5a + 1) = 16a^2
<=> c = -5a và b = -4a và - 20a^2 + 4a = 16a^2
<=> c = -5a và b = -4a và 36a^2 - 4a = 0
<=> c = -5a và b = -4a và a = 0 (loại) hay a = 1/9 (nhận)
Với a = 1/9 => b = -4/9 và c = -5/9
Vậy (P): y = x^2/9 - 4x/9 - 5/9